2009
DOI: 10.1007/s10549-009-0647-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary energy availability affects primary and metastatic breast cancer and metformin efficacy

Abstract: Dietary energy restriction has been shown to repress both mammary tumorigenesis and aggressive mammary tumor growth in animal studies. Metformin, a caloric restriction mimetic, has a long history of safe use as an insulin sensitizer in diabetics and has been shown to reduce cancer incidence and cancer-related mortality in humans. To determine the potential impact of dietary energy availability and metformin therapy on aggressive breast tumor growth and metastasis, an orthotopic syngeneic model using triple neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 43 publications
2
75
0
1
Order By: Relevance
“…Animal studies in other cancers have also evaluated the relationship between obesity and efficacy of metformin and found similar results to ours [76][77][78]. In particular, in both lung and breast cancer animal models, metformin was found to be more effective in decreasing tumor growth in animals fed a HFD compared to a low fat or standard diet [79,80]. Furthermore, in a randomized, placebo-controlled preoperative window study in breast cancer patients, women with higher body mass index (BMI) and Homeostatic Model Assessment of Insulin Resistance (HOMA) indexes had a greater response to metformin as evidenced by a decrease in Ki-67 staining [81].…”
Section: Discussionsupporting
confidence: 75%
“…Animal studies in other cancers have also evaluated the relationship between obesity and efficacy of metformin and found similar results to ours [76][77][78]. In particular, in both lung and breast cancer animal models, metformin was found to be more effective in decreasing tumor growth in animals fed a HFD compared to a low fat or standard diet [79,80]. Furthermore, in a randomized, placebo-controlled preoperative window study in breast cancer patients, women with higher body mass index (BMI) and Homeostatic Model Assessment of Insulin Resistance (HOMA) indexes had a greater response to metformin as evidenced by a decrease in Ki-67 staining [81].…”
Section: Discussionsupporting
confidence: 75%
“…In 1914, Payton Rous was the fi rst to suggest that restricted food intake reduced tumor growth by reducing the tumor blood supply ( 42 ). More recently, it has been suggested that CR reduces growth and angiogenic biomarker expression in prostate cancer and breast cancer (43)(44)(45)(46). The combination of CR and the KD [calorie restricted KD (RKD)] has also been studied as a cancer therapy.…”
Section: The Kd and Caloric Restriction In Preclinical Studiesmentioning
confidence: 99%
“…Conversely, Metformin (a mitochondrial complex I inhibitor) 47 should prevent cancer cells from effectively using mitochondrial fuels by inhibiting OXPHOS in cancer cells, inducing the conventional Warburg effect in cancer cells. [48][49][50][51][52] In fact, all three drugs have been shown to function as anticancer agents and also are associated with increased lifespan in studies of longevity. [53][54][55][56][57][58][59][60][61][62][63][64][65][66] So, a global whole-body approach to normalizing energy balance may prevent both aging and cancer, simultaneously.…”
Section: Visualizing Two-compartment Tumor Metabolism: Hyperactivatiomentioning
confidence: 99%